Hydraulic Structures in Water Aeration Processes - Baylar, Ahmet; Unsal, Mehmet; Ozkan, Fahri (Springer, 2010)
The primary purpose of water aeration is to increase the oxygen saturation of the water. This can be achieved by using hydraulic structures because of substantial air bubble entrainment at these structures. This paper reviewed the literature on hydraulic structures used in water aeration processes. The hydraulic structures were divided into two groups as the high-head flow systems and the free-surface flow systems. The high-head flow systems were circular and venturi nozzles, pipe with venturi tube, and high-head conduit, and the free-surface flow systems were weir, stepped cascade, and free-surface conduit. Air/water flow ratio and aeration efficiency in circular nozzles with air holes and venturi nozzles were significantly high. Pipes with venturi tubes showed high aeration efficiency although they had low air/water flow ratio. In high-head and free-surface conduits, almost full oxygen transfer, up to the saturation value, occurred. Forty-five degrees triangular sharp-crested weir had significantly better air/water flow ratio and aeration efficiency than other sharp-crested weir shapes. Stepped cascades, in particular nappe flow regime, were very efficient means of aeration.
Keywords: Aeration; Air/water flow; Free-surface flow; High-head flow; Oxygen transfer